UJI KANDUNGAN UNSUR RADIOAKTIF DAN BAKTERI PENCEMAR ESCHERICHIA COLI PADA LIMBAH INDUSTRI DI DAERAH HILIR SUNGAI BADUNG, DESA PEMOGAN - Suandewi, Ni Made Indah; Ratnawati, I Gusti A.A.; Darmayasa, Ida Bagus Gede (BULETIN FISIKA, 2015)
The radioactive element content and E.coli bacterial contaminants has been done testing in river water downstream of Badung River, Village Pemogan. The testing of elements content in the samples using AAS instrument (Atomic Absorption Sphectrometer) Analytical Laboratory Udayana University. The elements contained in the river water downstream of Badung River, Village Pemogan including Co, Cu, Pb, and Cd. The pollution in Badung river water to the elements thought due to the disposal of waste production by the textile dye industry was around the River Badung, Pemogan village. The test pollutant content of E.coli bacteria using the MPN (Most Probable Number). The results of the test bacteria by MPN method showed the presence of E.coli bacteria contaminants in Badung river water with amounts ranging from 0 to >11,000 samples MPN/100ml. According to PP 82 in 2001, the content of E.coli bacteria in the water of the river is allowed a maximum in the range of 2000 MPN/100ml water. This suggests that the content of E.coli bacteria in river water downstream of Badung River, Village Pemogan has exceeded a predetermined threshold. Keywords : Radioactive Elements, E.coli , AAS (Atomic Absorption Sphectrometer), MPN (Most Probable Number)